KEPENTINGAN AMERIKA SERIKAT MEMBERIKAN BANTUAN LUAR NEGERI “FEED THE FUTURE” KEPADA NEGARA SENEGAL TAHUN 2010-2015 - Muhammad, Fadel; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
A nation was formed with the ultimate aim of prospering the people who were part ofthe country. But foreign aid is a really strange phenomenon. A country consciously provide itsresources to improve the living conditions of people from other countries. Moral cause as theleader of countries in the world is the reason often announced every time the foreign assistanceis given. In fact, the often said foreign aid based on morality provide a form of reciprocityafterwards, such as political support, military base licensing, market expansion, and so on. Anoverseas aid program will go through a long process determined by the donor country (giver)such as which country will get it, how much the value of the foreign assistance is given, howlong is the aid-giving periods, and how to give it, in bilateral or multilateral. So is the casewith the food aid program “Feed the Future” given by the United States to the country ofSenegal in 2010-2015. Although on the surface, United States aid appears to have a goal tosolve Senegal’s food problems, but the United States has another big goal behind it. Resonancewith the theory expressed by Lancaster that one of the goals of providing foreign aid is as adiplomatic means in achieving interests in other countries, it is certain that the United Stateswill benefit from Senegal. Judging from the time of the provision of foreign aid which coincidedwith the issuance of the United States strategy in combating terrorism, it was certain thatforeign aid would reciprocate in the form of Senegal’s support for the national interests of theUnited States to combat violent groups in the West African region.Keywords: Foreign aid, National interests, Violent groups in West Africa, Food scarcity